2001
DOI: 10.1016/s1083-8791(01)80013-6
|View full text |Cite
|
Sign up to set email alerts
|

T-cell recovery in adults and children following umbilical cord blood transplantation

Abstract: T-cell reconstitution following allogeneic stem cell transplantation may involve thymic education of donor-derived precursors or peripheral expansion of mature T cells transferred in the graft. T cell-receptor excision circles (sjTRECs) are generated within the thymus and identify new thymic emigrants and those that have not divided. We measured quantitative and qualitative immunologic reconstitution and sjTREC levels in adult and pediatric recipients of umbilical cord blood transplants (UCBTs). sjTRECs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 41 publications
6
91
3
Order By: Relevance
“…Several reports outlining the kinetics of immune recovery after UCB transplantation in adults and children point to slow T-cell recovery [60], [62][63][64][65][66] compared with published reports after conventional graft allogeneic transplantation [66][67][68][69][70][71]. Recent studies have evaluated the immune function of adult UCB patients during the first two years post-transplant.…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports outlining the kinetics of immune recovery after UCB transplantation in adults and children point to slow T-cell recovery [60], [62][63][64][65][66] compared with published reports after conventional graft allogeneic transplantation [66][67][68][69][70][71]. Recent studies have evaluated the immune function of adult UCB patients during the first two years post-transplant.…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%
“…The mechanism and significance of this B-cell 'rebound' phenomenon observed post-transplant in adult UCB recipients is unclear. Work from the Duke University program reported that T-cell recovery was comparable in adults and children following UCB transplant [64]. This event was associated with delayed emergence of thymic recent emigrants cells (TREC) in adults (18 months) vs. children (12 months) as well as lower levels than expected for age.…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%
“…Children have more enhanced recovery of naı¨ve T cells (CD4 þ CD45RA þ ), greater thymic rebound, more diverse TCR, and higher TREC levels than their adult counterparts. [33][34][35] Faster CD4 þ recovery has been correlated with better protection against infection in pediatric vs adult T-cell-depleted BMT 36 and overall patient outcome in peripheral blood stem cell transplantation (PBSCT) from HLA-identical siblings or alternative family donors. 37 Second, pediatric patients seem to have less incidence of GVHD when compared to their adult counterparts.…”
Section: Ir Following Hsctmentioning
confidence: 99%
“…Functional immune recovery begins 3 months after conventional UCBT in adult patients, and T-cell reconstitution begins by 18 months. 29 Table 3 Phenotypic analysis of peripheral lymphocytes at the onset of tuberculosis Tuberculosis after RI-UCBTChronic GVHD, immunosuppressive therapy, TBI and Tcell depletion have been shown to be risk factors for tuberculosis following conventional allo-HSCT. 16,17,30 We used a TBI-containing preparative regimen, and two patients developed either GVHD or pre-engraftment immune reaction, requiring corticosteroid.…”
Section: Discussionmentioning
confidence: 99%